Computer Science Stack Exchange is a question and answer site for students, researchers and practitioners of computer science. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It's been a while since I had to solve a recurrence and I wanted to make sure I understood the iterative method of solving these problems. Given:

$$T(n) = 3T(n-2)$$

My first step was to iteratively substitute terms to arrive at a general form:

$$T(n-2) = 3T(n-2 -2) = 3T(n-4)$$ $$T(n) = 3 *3T(n-4)$$

leading to the general form:

$$ T(n) = 3^k T(n-2k) $$

Now I solve $n-2k = 1$ for $k$, which is the point where the recurrence stops (where $T(1)$) and insert that value ($n/2 - 1/2 = k$) into the general form:

$$T(n) = 3^{n/2-1/2}$$ $$T(n) = O(3^n)$$

I'm not sure about that last step:

I would just "argue" that as $n \to \infty$ one can ignore $-1/2$ and $n/2 \to n$ ? Is that assumption correct?

share|cite|improve this question
up vote 6 down vote accepted

Note that $3^{n/2-1/2} = \frac{1}{\sqrt{3}} 3^{n/2} = \frac 1{\sqrt{3}} \sqrt{3^n}$. So the $-\frac 12$ indeed becomes a constant factor that is absorbed by the $O()$, but $\frac n2$ in the exponent changes the base and changing the base changes the $O$-class.

The correct answer thus is $T(n) = O(3^{n/2}) = O(\sqrt{3^n})$.

share|cite|improve this answer
Thank you both @FrankW and @Jared! I marked this answer as correct because it contains an explanation (changing the base changes O-class). – wpp May 1 '14 at 11:36

Everything was correct up until the last found:

$$ T(n) \propto 3^{\frac{n}{2}- \frac{1}{2}} = \left(3^{n - 1}\right)^{\frac{1}{2}} = \frac{1}{\sqrt{3}}\left(\sqrt{3}\right)^n $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.